An ellipse with two focuses : towards a new theological method from Gaudium et Spes (Teología, 2019)
During the development of Vatican II, the systematic form in which thoughtand belief should shape each other was the object of important debates,specifically due to the novelty represented by the introduction of the inductivemethod in ecclesiastical teaching. It was realized that this innovationincluded a challenging reflection about the Church’s self-understanding, andtherefore a crucial debate about the goals of the Council itself. Such method,which later on was questioned, has been particularly relevant in the Latinamericanpost Council. Today, at stake are the chances that the Church,faith and theology become less indifferent to the unease that emerges fromthe complex biographic experiences and to the outcry that bursts out of theworld of suffering and from the poor.
Keywords: Signs of the times; Pastoral constitution; Inductive method